2011
DOI: 10.1111/j.1442-200x.2010.03192.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of sodium during formation of edema in children with nephrotic syndrome

Abstract: Although TBW increases in children with SSNS, intravascular volume is normal. In addition, hypoalbuminemia and sodium retention of the proximal tubule cause edema in children with SSNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 28 publications
2
14
0
3
Order By: Relevance
“…Our results confirmed the studies that demonstrated the importance of sodium reabsorption in proximal tubuli for the development of edema. Gurgoze et al (13) identified intrarenal sodium reabsorption in the pathogenesis of edema in NS. Vande Welle et al (14) detected that the rate of distal tubular potassium-sodium exchange is markedly higher in favor of sodium retention in cases of hypovolemic NS, while in nonhypovolemic patients they did not detect such a significant impact of the distal tubule, in accordance with our results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results confirmed the studies that demonstrated the importance of sodium reabsorption in proximal tubuli for the development of edema. Gurgoze et al (13) identified intrarenal sodium reabsorption in the pathogenesis of edema in NS. Vande Welle et al (14) detected that the rate of distal tubular potassium-sodium exchange is markedly higher in favor of sodium retention in cases of hypovolemic NS, while in nonhypovolemic patients they did not detect such a significant impact of the distal tubule, in accordance with our results.…”
Section: Discussionmentioning
confidence: 99%
“…For the estimation of circulating blood volume, IVCCI and LAD have been reported as valuable predictive factors. Decreased IVCCI and/or increased LAD indicate the increased volemic status in patients (12,13,21,22). Increased LVMI is defined as an increase in the mass of the left ventricle, which can be secondary to an increase in wall thickness, an increase in cavity size, or both.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing patients with and without edema, it was determined that their left atrial diameter and IVCCI values were similar. Moreover, patients with NS tended to be normovolemic instead of being hypovolemic (28). ANP and cGMP are biomarkers used to determine volume load for patients with conditions such as cardiac valve diseases and congestive heart failure affecting the left atrium.…”
Section: Discussionmentioning
confidence: 99%